2023
DOI: 10.1177/13607804221148836
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Interaction and Practices of Intimacy Among Emirati Young Spouses: Exploring the Experiences of Wives

Abstract: This study aims to explore the practices of intimacy among Emirati spouses in a society where gender discrimination persistently governs the private space of family relationships. Participants include 41 young Emirati working wives aged 24–30 who have jobs and are enrolled in graduate studies and research degrees (PhD and MA). In-depth interviews were used to collect data. Line-by-line coding, thematic coding, and constant comparison method were employed to analyze and interpret data. Analyses revealed seven i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…One of the main challenges faced by women in leadership is gender bias (Babalola, du Plessis, & Babalola, 2021;Diehl, Stephenson, Dzubinski, & Wang, 2020). Studies have shown that gender stereotypes are deeply ingrained in our culture, and these stereotypes often influence the way people perceive women in leadership positions (Al Hourani, 2023;Birindelli, Iannuzzi, & Savioli, 2019;Nickerson & Goby, 2017;Tabassum & Nayak, 2021). Women are often viewed as emotional, irrational, and less competent than their male counterparts, which can make it difficult for them to gain respect and credibility in their roles as leaders (Post & Sen, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the main challenges faced by women in leadership is gender bias (Babalola, du Plessis, & Babalola, 2021;Diehl, Stephenson, Dzubinski, & Wang, 2020). Studies have shown that gender stereotypes are deeply ingrained in our culture, and these stereotypes often influence the way people perceive women in leadership positions (Al Hourani, 2023;Birindelli, Iannuzzi, & Savioli, 2019;Nickerson & Goby, 2017;Tabassum & Nayak, 2021). Women are often viewed as emotional, irrational, and less competent than their male counterparts, which can make it difficult for them to gain respect and credibility in their roles as leaders (Post & Sen, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Another challenge faced by women in leadership is the lack of representation and mentorship (Al Hourani, 2023;Birindelli et al, 2019;Nickerson & Goby, 2017;Tabassum & Nayak, 2021). Women are often underrepresented in leadership positions, which can make it difficult for them to find role models and mentors who can guide them in their careers (Delgado & Ozuna Allen, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations